Controlled comparative clinical trial of hearing benefit outcomes for users of the Cochlear™ Nucleus® 7 Sound Processor with mobile connectivity - Warren, Chris D.; Nel, Esti; Boyd, Paul J. (Cochlear implants international, 2019)
Objectives: To assess subjective benefits and objective speech recognition performance following a take-home trial with the new Cochlear™ Nucleus ® 7 Sound Processor (SP), in experienced users of compatible cochlear implants from Cochlear Limited. Methods: A total of 37 adult participants were fitted with the Nucleus 7 SP and used the device for up to one year. Baseline speech recognition was assessed at the initial fitting session, using each participant's own SP, and Client Oriented Scale of Improvement (COSI) goals were identified. Speech recognition was measured after 3 months of device use and outcomes of the COSI and a non-validated Processor Comparison Questionnaire (PCQ) were collected. After 11 months, a subset of subjects were tested on speech recognition delivered via direct wireless streaming from an Apple ® smartphone to the SP and compatible hearing aid on the opposite side (if worn). Results: The COSI and PCQ instruments both indicated significant improvement in perceived subjective benefits in comparison to the participants' previous SPs. Direct streaming via an Apple mobile phone showed improvements when compared with the acoustic alone condition. Standard speech recognition in quiet and noise was equivalent to that obtained using a previous generation SP which uses the same basic processing as the Nucleus 7 Sound Processor. Conclusions: The incremental refinements provided by the Nucleus 7 Sound Processor provide real-world benefits in key areas such as upgraded wireless connectivity. The COSI proved to be an effective tool for individualized assessment of specific benefits that may not be addressed by more standardized instruments.